Activated O2•− and H2O2 Mediated Cell Survival in SU11274-Treated Non-Small-Cell Lung Cancer A549 Cells via c-Met-PI3K-Akt and c-Met-Grb2/SOS-Ras-p38 Pathways - Ying Liu; Qi-Feng Shi; Yuan-Chao Ye; Shin-ichi Tashiro; Satoshi Onodera; Takashi Ikejima (Elsevier, 2012)
The pharmacological activity of SU11274 is primarily due to its inhibition of hepotocyte growth factor receptor (c-Met) kinase overexpression. In this study, we demonstrated that the pathway involved in SU11274-induced autophagy was presumably through inhibition of c-Met and its down-stream pathways, including phosphatidylinositol 3-kinases - Akt (PI3K-Akt) and the growth factor receptor bound protein-2 / son of sevenless - Ras - p38 MAPK (Grb2/SOS-Ras-p38) pathway. SU11274 time-dependently induced the generation of superoxide anion (O2•−) and hydrogen peroxide (H2O2). There is a negative feedback loop between reactive oxygen species (ROS) induction and SU11274. Then, we investigated the role of ROS in protecting cells against SU11274-induced autophagic cell death in A549 cells. O2•− and H2O2 generation activated c-Met-PI3K-Akt and c-Met-Grb2/SOS-Ras-p38 signaling pathways, which were suppressed by O2•− scavenger superoxide dismutase (SOD) and H2O2 scavenger catalase. In conclusion, O2•− and H2O2 evoked cell resistance to SU11274 via activating c-Met-PI3K-Akt and c-Met-Grb2/SOS-Ras-p38 pathways in A549 cells. SU11274 also induced ROS generation in Caenorhabditis elegans. Keywords:: SU11274, superoxide anion, hydrogen peroxide, c-Met, A549 cell